Environmental friendly synthesis of hierarchical mesoporous platinum nanoparticles templated by fucoidan biopolymer for enhanced hydrogen evolution reaction. (1st June 2020) - Lim, Seung Man; Kang, Kyunglee; Jang, Hongje; Park, Jung Tae
Abstract: Researching novel hydrogen evolution reaction (HER) catalysts with enhanced electrocatalytic activity, excellent stability, and cost-efficiency is of great significance for the large-scale hydrogen production from industrial electrolysis technology. We report the preparation of hierarchical mesoporous-Pt nanoparticles (HM-PtNPs) with coral-like rough surface morphologies using environmental friendly and biocompatible fucoidan (Fu) biopolymer as a surface engineering compound and its application to electrocatalysts for water-splitting. The designed HM-PtNPs yields better mass activity of electrocatalysts compared to a commercial Pt/C. HM-PtNPs showed an overpotential of 33 mV at 10 mA cm −2 for the HER in 0.5 M H2 SO4, which was highly comparable to that of the commercial Pt/C catalysts (29 mV). However, the amount of HM-PtNPs loaded in glassy carbon electrode (0.033 mg mL -1 ) was approximately 20 times lower than that of the commercial Pt/C (0.64 mg mL -1 . The HM-PtNPs also maintained high catalytic stability with a consistent HER current density after 1000 continuous operation. The excellent HER performance is attributed to the improved electrochemical surface area, highly porous structure, and good surface wettability of the HM-PtNPs, which results in enhanced electrocatalytic activity, decreased resistance at the electrode/electrolyte interface, and facile penetration of the electrolytes inside the electrode.